2020
DOI: 10.21203/rs.3.rs-76711/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Covid-19 on Anxiety, Quality of Work Life and Fatigue of Health Care Providers in Health Care Centers

Abstract: Background and Aim: The aim of this study was to investigate the effect of Covid-19 on anxiety, quality of work life and fatigue of health center staff in southwestern Iran. Materials and Methods: The present study was a descriptive comparative study and the statistical population of the study included the staff of health centers of Shahrekord University of Medical Sciences. Using random sampling method, 181 people who had direct involvement with patients with Covid-19 were selected and compared with 261 staff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
0
11
0
2
Order By: Relevance
“…Another study conducted by Pavlović et al (2017) indicated that nurses in the surgical ward tended to be overloaded with work, leading to poor QWL and the likelihood of chronic stress. However, in a cross‐sectional survey conducted by Dehkordi et al (2020), health care providers reported decreased QOL upon the direct involvement or even without direct contact with COVID‐19 patients, and their fatigue and anxiety increased due to the pandemic. Stress or other psychological issues incurred by the nurses in their workplaces often lead to poor satisfaction with the job, incompetent work behaviour and a decreased quality of patient care (Khamisa et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted by Pavlović et al (2017) indicated that nurses in the surgical ward tended to be overloaded with work, leading to poor QWL and the likelihood of chronic stress. However, in a cross‐sectional survey conducted by Dehkordi et al (2020), health care providers reported decreased QOL upon the direct involvement or even without direct contact with COVID‐19 patients, and their fatigue and anxiety increased due to the pandemic. Stress or other psychological issues incurred by the nurses in their workplaces often lead to poor satisfaction with the job, incompetent work behaviour and a decreased quality of patient care (Khamisa et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that during the COVID-19 pandemic, healthcare providers had moderate compassion satisfaction, job burnout, and secondary traumatic stress 38 . These ndings are due to the fact that nurses are in the frontline of care delivery to patients with COVID-19 and hence, are at great risk for psychological disorders such as depression, which in turn increases their fatigue and reduces their PQOL 39 . Moreover, the mean score of compassion satisfaction in the present study was relatively greater than the mean score of nurses' compassion satisfaction in studies conducted before the COVID-19 pandemic 22,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Mental strain in such people could stem from having to use inadequate PPE, in addition to which a lack of respect from the community has been reported (Sun et al, 2020, p. 2). The pandemic impacted mental well-being with individuals reporting symptoms of anxiety, depression, insomnia, and stigma (Khanal et al, 2020), and a diminished psychological state was seen to have a negative effect on the QoL of medical staff (Dehkordi, 2020). Moreover, such a state in employees caused by exposure to the COVID-19 virus was negatively associated with the quality of life at work (Buselli et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%